2013
DOI: 10.1371/journal.pgen.1003356
|View full text |Cite
|
Sign up to set email alerts
|

Crif1 Deficiency Reduces Adipose OXPHOS Capacity and Triggers Inflammation and Insulin Resistance in Mice

Abstract: Impaired mitochondrial oxidative phosphorylation (OXPHOS) has been proposed as an etiological mechanism underlying insulin resistance. However, the initiating organ of OXPHOS dysfunction during the development of systemic insulin resistance has yet to be identified. To determine whether adipose OXPHOS deficiency plays an etiological role in systemic insulin resistance, the metabolic phenotype of mice with OXPHOS–deficient adipose tissue was examined. Crif1 is a protein required for the intramitochondrial produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 61 publications
5
60
0
Order By: Relevance
“…These findings supported the hypothesis that skeletal muscle mitochondrial deficiency does not mediate insulin resistance [25]. Collectively, although these gene manipulation studies revealed rather universal results, they require attention during interpretation because they casually reflect extreme cases that might lead to the activation of other compensatory mechanisms.…”
Section: Relationship Between Mitochondrial Function and Insulin Resisupporting
confidence: 74%
“…These findings supported the hypothesis that skeletal muscle mitochondrial deficiency does not mediate insulin resistance [25]. Collectively, although these gene manipulation studies revealed rather universal results, they require attention during interpretation because they casually reflect extreme cases that might lead to the activation of other compensatory mechanisms.…”
Section: Relationship Between Mitochondrial Function and Insulin Resisupporting
confidence: 74%
“…Numbers under the lanes are esi-2.1 levels normalized to luc knockdown. (F) S2 cells were treated with dsRNAs targeting luciferase (luc; negative control), Dcr-2, and dCRIF, respectively, and then the cell lysates were incubated with p 32 , dCRIF EY03252 heterozygous flies of the same age were infected with DCV and the viral load was quantified by qPCR amplification of viral RNA. The rp49 gene was used as a control.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, many different functions have been reported for mammalian CRIF1, including functions as a transcription co-factor and functions in mitochondria. [29][30][31][32][33] We are currently investigating the functions of dCRIF and its role in Dcr-2 stability.…”
Section: Discussionmentioning
confidence: 99%
“…As the variations in our mini-pig model were mainly restricted to highrespiratory tissues (brain, diaphragm, muscle, liver, heart, and fat), this suggests that there is epigenetic regulation of variant load to ensure the regulation of OXPHOS performance, which is reflected by higher mtDNA copy number (Kelly et al 2012;St John 2014). For example, for adipose tissue, this would link OXPHOS regulation to adipogenesis (Hofmann et al 2012), insulin metabolism (Ryu et al 2013), and thermogenesis (Duteil et al 2014).…”
Section: Discussionmentioning
confidence: 99%